THE SOLUTION OF PROCESS COST PROBLEMS. - Gordon, Dennis (The Accounting Review, 1949)
The article presents a solution of process cost problems. Students visualize and solve problems in process cost accounting more readily if they are taught to use a simple bar diagram. Actually the diagram is a restatement of the cost-of-goods-sold equation taught in elementary accounting. The cost of the beginning inventory plus the material, labor and overhead put into production during the period equals the cost of the finished goods plus the work in process at the end of the period. This statement is true whether or not there has been any spoilage or shrinkage during the processing period, because the loss is absorbed by the good units produced. After the instructor has introduced and illustrated the concept of finished unit equivalents, he is ready to work a simple problem. In solving this problem, the student can immediately see that the value of the finished units plus the work remaining in process at the end of the period must total $188,000. How should this amount be divided between finished goods and work in process? Then compute the finished unit equivalent, which simply means the number of fully finished units that would have been manufactured if there were no beginning or ending inventories of work in process.